1996
DOI: 10.1101/gad.10.4.478
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor Spo0A switches the localization of the cell division protein FtsZ from a medial to a bipolar pattern in Bacillus subtilis.

Abstract: Entry into sporulation by the Gram-positive bacterium Bacillus subtilis is governed by two transcription factors, SpoOA and cr H, and involves a switch in the site of division from a medial to a polar location. We report that at the onset of sporulation, assembly of the cell division protein FtsZ shifts from midcell to potential division sites near both poles. The switch to a bipolar pattern of FtsZ localization is dependent on Spo0A. Additionally, synthesis of an activated form of Spo0A during growth artifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
264
3
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(285 citation statements)
references
References 58 publications
16
264
3
2
Order By: Relevance
“…Counterstaining to visualize DNA was achieved by adding a final concentration of 10 g ml ¹1 propidium iodide 10 min before the end of the secondary antibody incubation. Under our labelling conditions, propidium iodide only labels DNA because the RNA is degraded by a contaminating RNase in the lysozyme (Levin and Losick, 1996). We confirmed that the intensity of staining by propidium iodide was not affected by treating the cells with RNase (not shown).…”
Section: Microscopysupporting
confidence: 73%
“…Counterstaining to visualize DNA was achieved by adding a final concentration of 10 g ml ¹1 propidium iodide 10 min before the end of the secondary antibody incubation. Under our labelling conditions, propidium iodide only labels DNA because the RNA is degraded by a contaminating RNase in the lysozyme (Levin and Losick, 1996). We confirmed that the intensity of staining by propidium iodide was not affected by treating the cells with RNase (not shown).…”
Section: Microscopysupporting
confidence: 73%
“…The symmetrical position of the vegetative division septum, as indicated by the FtsZ band, was not surprising. In contrast, the symmetrical location of the septum in sporulating S. ureae was surprising, because it was strikingly different from the asymmetrical location observed for sporulating B. subtilis (Levin and Losick, 1996). Several lines of evidence make us confident that we were indeed observing sporulating cells (as distinct from vegetative cells): (i) the cells were expressing spoIIA-lacZ, which is an early sporulationspecific event; (ii) the cells expressing ␤-galactosidase from the spoIIA-lacZ fusion were only observed in samples taken after the end of exponential growth -as with B. subtilis, the end of exponential growth is defined as the start of sporulation; (iii) no subsequent division was observed during sporulation of S. ureae.…”
Section: Discussionmentioning
confidence: 69%
“…1A). Since FtsZ protein assembles at the site of septum formation, the band is presumed to indicate a cell division occurring perpendicular to the plane of the image, as has been observed with B. subtilis (Levin and Losick, 1996) and Escherichia coli (Bi and Lutkenhaus, 1991;Addinall et al, 1996). The ring pattern is presumed to indicate a division in the plane of the image.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations